A global public health convention for the 21st century. (June 2021) - Duff, Johnathan H; Liu, Anicca; Saavedra, Jorge; Batycki, Jacob N; Morancy, Kendra; Stocking, Barbara; Gostin, Lawrence O; Galea, Sandro; Bertozzi, Stefano; Zuniga, Jose M; Alberto-Banatin, Carmencita; Dansua, Akua Sena; et al.
Summary: As shown by COVID-19, infectious diseases with a pandemic potential present a grave threat to health and wellbeing. Although the International Health Regulations provide a framework of binding legal obligations for pandemic prevention, preparedness, and response, many countries do not comply with these regulations. There is a need for a renewed framework for global collective action that ensures conformity with international regulations and promotes effective prevention and response to pandemic infectious diseases. This Health Policy identifies the necessary characteristics for a new global public health security convention designed to optimise prevention, preparedness, and response to pandemic infectious diseases. We propose ten recommendations to strengthen global public health governance and promote compliance with global health security regulations. Recommendations for a new global public health security convention include greater authority for a global governing body, an improved ability to respond to pandemics, an objective evaluation system for national core public health capacities, more effective enforcement mechanisms, independent and sustainable funding, representativeness, and investment from multiple sectors, among others. The next steps to achieve these recommendations include assembling an invested alliance, specifying the operational structures of a global public health security system, and overcoming barriers such as insufficient political will, scarcity of resources, and individual national interests.